Approach to Employment Planning in India - Planning Commission (Planning Commission Government of India, 1980)
J.I. Sinha’s Approach to Employment Planning in India provides a comprehensive analysis of the interrelationship between economic growth, unemployment, and poverty, emphasizing the need for structural reforms to generate sustainable employment. The document highlights that modest increases in national income have not effectively reduced chronic unemployment, particularly in urban areas, or poverty in rural regions dependent on agriculture. Employment planning is positioned as essential for equitable income distribution, social stability, and long-term economic productivity. Sinha critiques prior planning strategies and underscores the importance of targeted policies addressing low-skilled labor, gender equity, regional disparities, and productivity enhancement. The analysis of industrial policy reveals that small enterprises, though labor-intensive, have limited growth and wage potential, necessitating reinvestment and diversification. Additionally, the expansion of the services sector, including construction, transport, and trade, is identified as a significant avenue for non-agricultural employment. Policy recommendations include structural economic adjustments, agricultural diversification, promotion of labor-intensive industries, and strategic infrastructure development to foster sustainable employment, reduce poverty, and enhance income equity. The study concludes that achieving meaningful employment outcomes requires integrated, sector-specific, and regionally sensitive planning alongside enhanced government and community collaboration.
India Planning Commission
Keywords: Employment Planning; Unemployment; Poverty Alleviation; Economic Growth; Small Enterprises; Industrial Policy; Wage Dynamics; Agricultural Diversification; Services Sector; Regional Disparities; Income Inequality; Labor Productivity